2004
DOI: 10.1210/en.2003-1698
|View full text |Cite
|
Sign up to set email alerts
|

The Androgen-Regulated Epididymal Sperm-Binding Protein, Human β-Defensin 118 (DEFB118) (Formerly ESC42), Is an Antimicrobial β-Defensin

Abstract: Spermatozoa bind a variety of proteins as they pass through the proximal regions of the epididymis, where they acquire forward motility and fertilizing ability. Recent evidence indicates that certain epididymis-specific secretory proteins that bind sperm have antibacterial activity and may function as part of the innate immune system. We reported earlier that ESC42, now designated human beta-defensin 118 (DEFB118), is a sperm-binding protein. In this study, we demonstrate that DEFB118 has potent antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 69 publications
3
88
2
5
Order By: Relevance
“…4 Although the 20q defensins are structurally distinct from DEFB1 and DEFB2, they maintain the cationic property of the defensin signature six-cysteine array that is essential for antimicrobial action. 29 The antibacterial property is likely to be conserved throughout the cluster since the lead member, DEFB118, displays this activity 26 and the human 20q genes and macaque orthologs show greater sequence conservation than the members of other defensin clusters. Defensins of the 20p cluster exhibit long C-terminal domains in contrast to the 8p cluster short C-terminal domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Although the 20q defensins are structurally distinct from DEFB1 and DEFB2, they maintain the cationic property of the defensin signature six-cysteine array that is essential for antimicrobial action. 29 The antibacterial property is likely to be conserved throughout the cluster since the lead member, DEFB118, displays this activity 26 and the human 20q genes and macaque orthologs show greater sequence conservation than the members of other defensin clusters. Defensins of the 20p cluster exhibit long C-terminal domains in contrast to the 8p cluster short C-terminal domains.…”
Section: Discussionmentioning
confidence: 99%
“…20 Previously, we identified the novel epididymal spermbinding protein DEFB118 25 and recently showed that DEFB118 has potent antibacterial activity. 26 The potential importance of the male reproductive tract defensins in host defense as well as male reproductive functions prompted us to investigate the 20q b-defensin gene cluster. Herein we present the characterization and evolutionary analysis of human and macaque b-defensin orthologs, which give new insights into adaptive functional roles.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we described the epididymal sperm binding protein DEFB118, a potent antibacterial agent and lead member of the ␤-defensin gene cluster on human chromosome 20q (38,54,81). Here, we report the discovery and characterization of the orthologous cluster in mouse.…”
mentioning
confidence: 93%
“…29 The C-terminal Histag might reduce the antibacterial potency of b-defensin 22, although the physiological significance of the long C-terminal domain remains unclear.…”
mentioning
confidence: 99%